Tren Inovasi dan Dampak Transit Oriented Development dalam Mobilitas Masyarakat Perkotaan Terhadap Bus Trans Mamminasata di Kota Makassar - Lestari, Nina; Nurdiansyah B, Aldy (Universitas Muhammadiyah Makassar, 2024)
Transit-Oriented Development (TOD) in Makassar: Enhancing Sustainable Urban Mobility Transit-Oriented Development (TOD) emphasizes integrating residential, commercial, and public facilities around public transportation systems to create urban environments that reduce reliance on private vehicles. Makassar has taken significant steps toward sustainable development by adopting TOD principles through the innovative Mamminasata bus system. The Mamminasata bus network serves as the backbone of Makassar's public transportation system, connecting key areas across the city while promoting efficient and sustainable urban growth. By reducing dependency on private vehicles and improving access to various facilities, TOD driven by the Mamminasata bus system has positively impacted the environment, local economy, and social inclusivity. However, challenges such as low passenger occupancy rates, limited integration with other modes of transport, and inadequate infrastructure maintenance continue to affect the system's effectiveness. To enhance the TOD approach, solutions such as optimizing routes, improving infrastructure, developing supportive policies, and increasing community participation are crucial. By fostering greater public acceptance, providing better accessibility, and delivering tangible benefits, TOD in Makassar can transform urban mobility, promote sustainability, and create a more connected and prosperous city for all residents.